Amygdala enlargement and emotional responses in (autoimmune) temporal lobe epilepsy - Holtmann, Olga (Sci Rep, 2018)
Temporal lobe epilepsy with amygdala enlargement (TLE-AE) is increasingly recognized as a distinct adult electroclinical syndrome. However, functional consequences of morphological alterations of the amygdala in TLE-AE are poorly understood. Here, two emotional stimulation designs were employed to investigate subjective emotional rating and skin conductance responses in a sample of treatment-naïve patients with suspected or confirmed autoimmune TLE-AE (n = 12) in comparison to a healthy control group (n = 16). A subgroup of patients completed follow-up measurements after treatment. As compared to healthy controls, patients with suspected or confirmed autoimmune TLE-AE showed markedly attenuated skin conductance responses and arousal ratings, especially pronounced for anxiety-inducing stimuli. The degree of right amygdala enlargement was significantly correlated with the degree of autonomic arousal attenuation. Furthermore, a decline of amygdala enlargement following prompt aggressive immunotherapy in one patient suffering from severe confirmed autoimmune TLE-AE with a very recent clinical onset was accompanied by a significant improvement of autonomic responses. Findings suggest dual impairments of autonomic and cognitive discrimination of stimulus arousal as hallmarks of emotional processing in TLE-AE. Emotional responses might, at least partially, recover after successful treatment, as implied by first single case data.